Tingkat Pengaruh Gadget Terhadap Pola Belajar Siswa - Markus Prayoga Telaumbanua; Griyatri Lidya Laurenza Zebua (CV. SINAR HOWUHOWU, 2024)
The use of gadgets among students in increasing, affecting various aspects of the learning process. This research aims to analyze the impact of gadgets on student learning patterns, including concentration, motivation and learning effectiveness. By using survey and interview methods with secondary school students, this research found that gadgets can have both positive and negative influences on learning patterns. On the one hand, access to information via gadgets expands knowledge and supports independent learning. However, on the other hand, excessive or uncontrolled use can reduce focus and increase the risk of disoders, such as social media addiction. It is hoped that the results of this research can be a consideration for educators and parents in using gadgets wisely to support students learning process.